Heterocyclic chemistry - Gilchrist, T. L. ([S.l.] : Longman Group United Kingdom, 1993)
Provides an up-to-date survey of the various types of heterocyclic ring systems and describes the preparation and properties of compounds. "...a full treatment of heterocyclic chemistry, suitable for postgraduates and professionals as well as undergraduates." New Scientist.